Analysis of the Level of Transport Activities That Affect Operations - Janpet, Jatupon; Rianmahasan, Pisanu (Ph.D. in Social Sciences Journal, 2022)
The objective of the article was to develop the level of transportation activities of Small and Medium-sized Enterprises (SMEs). By measuring the level of activity in the form of U-models and I-models (Uppsala internationalization model & Internationalization model) for small business entrepreneurs Small and Medium-sized Enterprises (SMEs). and both knowledge and experience abroad, that have performed in terms of income, profit, market share, and market expansion to be more efficient. The results of the analysis found that Small and Medium-sized Enterprises (SMEs) engaged in transportation activities carried out transportation activities in the form of I-models, which is a measure of the level of transportation activities in 4 phases. Development and adaptation of entrepreneurs but nowadays, entrepreneurs need to expand the market to more foreign countries. Therefore, entrepreneurs who carry out activities by the I-Model model alone are not sufficient for operating results. It is necessary to bring the development model at the stage level together with the U-model at the level of bringing the process of both knowledge and skills and experience in the international market to be used as a guideline for Small and Medium-sized Enterprises (SMEs) to supplement. Create an organization’s growth strategy to compete effectively with foreign countries.